Policy capacities and effective policy design: A review - MUKHERJEE, Ishani (Institutional Knowledge at Singapore Management University, 2021)
Effectiveness has been understood at three levels of analysis in the scholarly study of policy design. The first is at the systemic level indicating what entails effective formulation environments or spaces making them conducive to successful design. The second reflects more program level concerns, surrounding how policy tool portfolios or mixes can be effectively constructed to address complex policy objectives. The third is a more specific instrument level, focusing on what accounts for and constitutes the effectiveness of particular types of policy tools. Undergirding these three levels of analysis are comparative research concerns that concentrate on the capacities of government and political actors to devise and implement effective designs. This paper presents a systematic review of a largely scattered yet quickly burgeoning body of knowledge in the policy sciences, which broadly asks what capacities engender effectiveness at the multiple levels of policy design? The findings bring to light lessons about design effectiveness at the level of formulation spaces, policy mixes and policy programs. Further, this review points to a future research agenda for design studies that is sensitive to the relative orders of policy capacity, temporality and complementarities between the various dimensions of policy capacity.